REPRESENTASI KETIDAKSETARAAN GENDER DALAM PROGRAM TELEVISI - restiawan permana (PRoMEDIA, 2016)
As a product of the media, talk shows can be culture 'text' that interacts with viewers in the production and exchange of meaning. Almost all programs talk shows on television to attract people to watch it. Indulgence of society in the program caused by several factors, such as the show that is entertaining, any informative, educative, and inspiring messages contained in the talk show. Moreover, were guided by a reliable host emceeing, or by bringing in a competent and influential resource for the community. In this study, the authors chose two talk shows to being the object of research. Both of these talk shows that "Tonight Show" and "Ini Talkshow 'which aired on NET TV. This study aims to describe how the representation of gender inequality in the program "Tonight Show" and "Ini Talkshow" on NET TV. This study used a qualitative approach, because the data were obtained and extracted from observations, the study of literature and documentation. The results of this study indicate In the course of the Tonight Show, gender inequality occurs between hosts with Co-Host. This indicates that the NET TV has represented the existence of gender differences and subordination between men and women. While the program's talk show, gender inequality occurs between Host/Co-Host with supporting other events. This indicates that the NET TV has represented the difference between gender and workload of men and women. Keywords: representation, gender inequality, talk show